Lithium, sodium, potassium and calcium amine-bis(phenolate) complexes in the ring-opening polymerization of rac-lactide. Issue 5 (13th January 2020) - Devaine-Pressing, Katalin; Oldenburg, Fabio J.; Menzel, Jan P.; Springer, Maximilian; Dawe, Louise N.; Kozak, Christopher M.
Abstract : Li, Na, K and Ca complexes capable of rac -lactide polymerization in both the melt and in solution were synthesized. MALDI-TOF MS showed mainly cyclic PLA was obtained even in the presence of an alcohol co-initiator. Abstract : Compounds of Li, Na, K and Ca of a tetradentate amino-bis(phenolato) ligand were prepared. Bimetallic compounds formulated as M2 [L ](THF) n (where M = Na, n = 1 (1 ·THF) or Li, n = 1 (2 ·THF)) were synthesized via the reaction of H2 [L ] (where [L ] = 2-pyridylmethylamino- N, N -bis(2-methylene-4-methoxy-6- tert -butylphenolato) with sodium hydride or n -butyllithium, respectively, in THF. Monometallic complexes MH[L ](THF) n (where M = Na, n = 1 (3 ·THF), Li, n = 0 (4 ) and K, n = 0 (5 )) were obtained by reaction of H2 [L ] with MN(SiMe3 )2 where M = Na, Li, or K. Calcium complex Ca[L ](THF) (6 ·THF) was synthesized in two ways; reaction of Na2 [L ] with calcium iodide in THF, and reaction of Ca[N(SiMe3 )2 ]2 with H2 [L ] in toluene. Compounds 1–6 exhibit activity for rac -lactide polymerization under melt and solution conditions. Moderate control of polymer molecular weights was achieved in toluene, whereas polydisperse polymer was obtained under solvent free conditions. MALDI-TOF MS analysis of the polymer end groups revealed a predominantly cyclic nature for the polylactides.